The politics of urban governance - Pierre, Jon. (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2011)
"This broad ranging new text analyses the emerging shape of urban politics in the twenty-first century. The author identifies 4 main "models" of urban governance--"management," "Corporatist." "Pro-Growth" and "Welfare"--and assesses their different implications for the major issues, interests and problems in the contemporary urban arena"--
Machine generated contents note: -- The Challenge of Urban Governance * Rethinking the Local State * The Managerial City * The Corporatist City * The Pro-Growth City * The Welfare City * The Decline of Urban Politics? * Cities in Global Governance * Conclusion: The Future of Urban Politics.
Includes bibliographical references (p. 154-164) and index.
Keywords: Municipal government -- Cross-cultural studies; Local government -- Cross-cultural studies; Political leadership -- Cross-cultural studies; Sociology, Urban -- Cross-cultural studies; Urban policy -- Cross-cultural studies; POLITICAL SCIENCE / Public Policy / General; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development; POLITICAL SCIENCE / Government / Local